An Analysis of Swear Words in “Once Upon a Time... In Hollywood” Film - Peggy Andriani Kakisina; Isti Purwaningtyas (IAIN MADURA, 2020)
Swear words are one of the linguistic choices which show cultural aspects. Found in both oral and written forms. Swear words represent emotions and convey powerful messages. Some people utter swear words because of specific reasons, and they occasionally ignore their literal meaning. The phenomenon of swearing also happens in films. Based on the film Once Upon a Time... in Hollywood, this qualitative research addressed the semantic referents of swear words and the motives of swearing. By employing content analysis, the results show that (a) 59 swear words are classified into nine semantic referents, consisting of offensive slang (17%) as the main referent, followed by profane or blasphemous (15%), psychological-physical-social deviations (15%), scatological and disgusting objects (15%), sexual references (12%), substandard vulgar terms (10%), ethnic-racial-gender slurs (7%), animal names (5%), and ancestral allusions (4%) and (b) swearing are caused by three motives, namely psychological, social, and linguistic. The study concludes that the film contains severe and various swear words, and particular situations can lead the characters to swear. General readers are hoped to be more considerate in expressing themselves and be wiser in determining their word choices